Hubungan antara Kepuasan Kerja dan Kinerja Pegawai Tenaga Kependidikan Universitas Brawijaya (Studi pada Tenaga Kependidikan PNS dan Non PNS di Rektorat Universitas Brawijaya) - Khuriyah, Dewi (Jurnal Ilmiah Administrasi Publik, 2019)
The purpose of this study was to analyze job satisfaction factors that affect the performance of employees in the Main Office (Rectorate) of Brawijaya University. Research method in this study is a quantitative method with a descriptive approach. The study was conducted at the Main Office of Brawijaya University with a population of 389 people. In this study, the sampling technique was probability sampling with proportionate stratified random sampling technique. The technique of collecting the data used a survey method with a questionnaire, while to measure the variables used a Likert scale. The data analysis used multiple linear regressionanalysis with the help of SPSS 23.0. The results of the study indicate satisfaction with salary, with the work itself, with work supervision, with colleagues has a positive and significant effect on the performance of employees, while satisfaction with promotion and satisfaction with the work environment has a positive and not significant effect on the performance of employees in the Main Office of Brawijaya University